2022
DOI: 10.1177/01492063221080125
|View full text |Cite
|
Sign up to set email alerts
|

Media Coverage of Earnings Announcements: How Newsworthiness Shapes Media Volume and Tone

Abstract: Media coverage of earnings is consequential for firms. As such, firms work hard to ensure their performance beats analyst estimates to avoid negative coverage. However, the relationship between performance and coverage might not be as straightforward as firms assume because media coverage is a socially constructed process that reflects journalists’ social and cognitive biases while producing newsworthy content. With this in mind, we unpack the concept of newsworthiness and develop theory regarding how the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 163 publications
0
7
0
Order By: Relevance
“…The above conclusions still hold after a series of robustness tests. Some financial information (e.g., earnings announcements) is relatively less accessible to the public due to information asymmetry and high processing costs relative to media coverage ( Oliver et al, 2022 ). In this regard, interpreting some information in making financial decisions is challenging for individuals who lack the relative financial literacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The above conclusions still hold after a series of robustness tests. Some financial information (e.g., earnings announcements) is relatively less accessible to the public due to information asymmetry and high processing costs relative to media coverage ( Oliver et al, 2022 ). In this regard, interpreting some information in making financial decisions is challenging for individuals who lack the relative financial literacy.…”
Section: Discussionmentioning
confidence: 99%
“…We argue that limited attention serves as an underlying mechanism in the association between financial literacy and households’ financial behavior. In fact, some financial information (e.g., earnings announcements) is relatively less accessible to the public due to information asymmetry and high processing costs relative to media coverage ( Oliver et al, 2022 ). For example, rural households with lower financial literacy may not actively participate in the financial market fairly and enjoy the benefits of financial services ( Mahendru, 2020 ; Xu et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The manner in which CSI events are portrayed (particularly by traditional media) can evoke stakeholders’ cognitions, biases and expectations (Deephouse & Heugens, 2009). The knowledge of stakeholder biases and expectations may, however, lead intermediaries to cover those firm behaviours which are most likely to trigger stakeholder cognition, as well as conflict with prior stakeholder expectations (see, more recently, Oliver et al., 2022). As such, firms may experience greater attention for CSI when they are considered ‘celebrities’ (Rindova et al., 2006; Zavyalova et al., 2017) or indeed, when they already own a highly positive corporate reputation (King & McDonnell, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The news media usually publish and comment on firms' financial performance and their participation in financial markets. Although effective media coverage can make the capital market much more efficient by alleviating information asymmetries and increasing firm exposure to market investors (Bushee et al, 2010; Fang & Peress, 2009; Guldiken et al, 2017; Oliver et al, 2023), studies have also shown that media coverage is somewhat biased and slanted by firms. Current studies suggest that positive media coverage can be used by firms as an important tool to manage the image of the focal firm (Baloria & Heese, 2018; Guo et al, 2021; Gurun & Butler, 2012; Wu & Yang, 2022).…”
Section: Introductionmentioning
confidence: 99%